Nep-Endotrainer: A cost-effective home-made laparoscopic simulation tool - Uttam Laudari (Society of Surgeons of Nepal, 2021)
Introduction: Laparoscopic surgery is an established treatment modality worldwide. Opportunities to acquire this skill using expensive simulation at workplace are not always feasible due to cost, time and accessibility constraints. Nep-Endotrainer is a cost effective homemade laparoscopic simulation tool built in Nepal.